Efektivitas Pelayanan Amenities Tamu oleh Section At Your Service pada Era Pandemi COVID-19 di Hotel The Westin Resort & Spa Ubud Bali - Anak Agung Istri Ratna Sari Wulan; I Kadek Arista Priana Ayusman; Ni Nyoman Suci Arthini (Journal of Hospitality Accommodation Management (JHAM), 2023)
The COVID-19 pandemic has made the government to make standard health protocols for tourism (CHSE) companies, one of which is a company engaged in accommodation. This study aims to determine the effectiveness of guest amenities services by section at your service in the era of the COVID-19 pandemic.This study uses two instruments, namely interview guidelines and an observation checklist. This study also uses two types of data analysis techniques, namely qualitative data analysis techniques and narrative analysis techniques. The subject of this study was employees at your service (AYS). During the research, it was found that several things were not suitable to be done according to the standards of amenities service at The Westin Resort & Spa Ubud Bali, including not updating the room occupancy rate and information in the system; have not checked the special guest request; not stand by to receive calls from guests who will be checking out; have not prepared amenities and welcome cards for VIP guests, special requests, and target promoters; not entering GXP cases and requests from guests; have not courtesy call and follow up to GXP if the guest reports problem.